Nanoscale mapping of nuclear phosphatidylinositol phosphate landscape by dual-color dSTORM - Hoboth, Peter; Sztacho, Martin; Šebesta, Ondřej; Schätz, Martin; Castano, Enrique; Hozák, Pavel (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Current models of gene expression, which are based on single-molecule localization microscopy, acknowledge protein clustering and the formation of transcriptional condensates as a driving force of gene expression. However, these models largely omit the role of nuclear lipids and amongst them nuclear phosphatidylinositol phosphates (PIPs) in particular. Moreover, the precise distribution of nuclear PIPs in the functional sub-nuclear domains remains elusive. The direct stochastic optical reconstruction microscopy (dSTORM) provides an unprecedented resolution in biological imaging. Therefore, its use for imaging in the densely crowded cell nucleus is desired but also challenging. Here we present a dual-color dSTORM imaging and image analysis of nuclear PI(4,5)P2, PI(3,4)P2 and PI(4)P distribution while preserving the context of nuclear architecture. In the nucleoplasm, PI(4,5)P2 and PI(3,4)P2 co-pattern in close proximity with the subset of RNA polymerase II foci. PI(4,5)P2 is surrounded by fibrillarin in the nucleoli and all three PIPs are dispersed within the matrix formed by the nuclear speckle protein SON. PI(4,5)P2 is the most abundant nuclear PIP, while PI(4)P is a precursor for the biosynthesis of PI(4,5)P2 and PI(3,4)P2. Therefore, our data are relevant for the understanding the roles of nuclear PIPs and provide further evidence for the model in which nuclear PIPs represent a localization signal for the formation of lipo-ribonucleoprotein hubs in the nucleus. The discussed experimental pipeline is applicable for further functional studies on the role of other nuclear PIPs in the regulation of gene expression and beyond.
Keywords: Nuclear speckles; RNA-polymerasa II; Cell Line, Tumor; Phosphatidylinositol Phosphates; Cell Nucleolus; RNA Polymerase II; fosfatidylinositolfosfáty; vedlejší histokompatibilní antigeny; Microscopy; Phosphatidylinositol phosphates; RNA polymerase II; DNA vazebné proteiny; lidé; mikroskopie; Humans; STORM; Minor Histocompatibility Antigens; Nucleolus; nádorové buněčné linie; DNA-Binding Proteins; buněčné jadérko; Cell nucleus